Perancangan Sistem Informasi Akademik Menggunakan Framework Codeigniter Pada Sma Negeri 2 Rambang Dangku Berbasis Web - Resti Amilia; Andi Christian; Khana Wijaya (STEKOM PRESS, 2023)
The purpose of the research conducted was to design an Academic Information System (SIAKAD) at SMA Negeri 2 Rambang Dangku. Data processing at SMA Negeri 2 Rambang Dangku has not utilized the use of information technology to support operational activities, data processing is still recorded manually, such as in processing student assessment data, teacher data, lesson schedule data and student final report data (Raport) and data storage is still done conventionally using paper and cabinets. In collecting data, researchers used qualitative descriptive methods including conducting interviews, direct observation, and literature study. The system development method uses the Prototype method. At the design stage using the Unified Modeling Language (UML) modeling which consists of use case diagrams, class diagrams, and activity diagrams. This system is built using PHP, Mysql, Xampp, and database. The results of this study are a web-based academic information system using the Codeigniter Framework. From this application it is hoped that it will make it easier to process Academic data for SMA Negeri 2 Rambang Dangku so that it is faster and more detailed, and makes it easier to make final data reports on student scores (Rapot).